Parâmetros genéticos, fenotípicos e seleção de híbridos experimentais de morangueiro - Vieira, Sylvia Dantas (2016)
In Brazil the breeding programs of strawberry plants did not achieve major advances over the past decades, this indicates that the country is still dependent on imported materials, not fully adapted to our climatic conditions. The objectives in this study were estimate the genetic and phenotypic parameters of experimental hybrids and check the efficiency of selection indexes to select experimental hybrids, to provide input for the breeding program of strawberry plants at the Federal University of Lavras (UFLA). Seven commercial cultivars were used and 103 experimental hybrids obtained selections in populations from the cross between them. The genetic parameters estimated general combining ability (GCA), specific combining ability (SCA), genotypic correlation between characters, estimate of heritability, Genetic and phenotypic variance. Analyses were performed with the aid of SAS software. For the selection of the following hybrid selection indexes were applied: Mulamba e Mock (1978), Smith (1936) e Hazel (1943) and Genotype-ideotype, selecting 20 % of genotypes in the experiment. The cultivars ‘Aromas’ and ‘Camarosa’ showed good combining ability and some correlations stood out (Total mass and number of commercial fruit, fruit weight and number of unmarketable fruits). For all selected hybrids, the three indices showed coincidence coefficient of approximately 9%, selecting two experimental hybrids (89 and 495). These results serve as a basis for decision-making in the breeding program of strawberry UFLA and UNICENTRO.